Chemical composition and fermentation characteristics of elephant grass silage with biodiesel industry co-products - Castello Branco van Cleef, Eric Haydt [UNESP]; da Silva Filho, Jose Cleto; Neiva Junior, Arnaldo Prata; Patino Pardo, Rene Mauricio; do Rego, Anibal Coutinho [UNESP]; Goncalves, Josemir de Souza (Universidade Federal de Santa Maria (UFSM), 2012)
The objective of this research was to evaluate the effect of three concentrations (3, 6, and 9%) of forage turnip (Raphanus sativus) and physic nut (Jatropha curcas) cakes on dry matter, crude protein, ether extract, neutral detergent fiber, acid detergent fiber, lignin, acid detergent insoluble nitrogen neutral detergent insoluble nitrogen contents, in vitro dry matter digestibility, pH values and concentrations of N-NH3 in elephant grass silages. It was used an entirely randomized design in factorial arrangement [(2x3)+1]. Experimental PVC silos were used and ensiled material was kept for 62 days. The addition of cakes increased the dry matter contents (P<0.05). The fibrous fractions were reduced (P<0.05) with the inclusion of cakes during the grass ensilage and the CP contents increased (P<0.05). The forage turnip cake provided the same pH and N-NH3 values in ideal levels and the physic nut, added to 9%, increased those values (P<0.05). IVDMD was reduced (P<0.05) when the cakes were added. These co-products can be used in small amounts for elephant grass ensilage in order to provide improvement in chemical and fermentation characteristics of the silages. Nevertheless, physic nut cake shows limitations for its use in animal feeding due to the presence of toxic compounds, making necessary studies for their identification and elimination.

Objetivou-se avaliar o efeito da adição de três concentrações (3, 6, e 9%) das tortas de nabo forrageiro (Raphanus sativus) e de pinhão manso (Jatropha curcas) sobre os teores de matéria seca, proteína bruta, extrato etéreo, fibra em detergente neutro, fibra em detergente ácido, lignina, nitrogênio insolúvel em detergente ácido, nitrogênio insolúvel em detergente neutro, digestibilidade in vitro da matéria seca, valores de pH e concentrações de N-NH3 em silagens de capim-elefante. Utilizou-se delineamento inteiramente casualizado em arranjo fatorial [(2×3)+1]. Foram utilizados silos experimentais de PVC e o material ensilado permaneceu por 62 dias. A adição das tortas proporcionou aumento nos teores de matéria seca (P<0,05). As frações fibrosas foram diminuídas (P<0,05) com a inclusão das tortas no momento da ensilagem do capim e os teores de PB aumentados (P<0,05). A torta de nabo forrageiro proporcionou a manutenção dos valores de pH e de N-NH3 em níveis ideais e a de pinhão manso, adicionada a 9%, elevou esses valores (P<0,05). A DIVMS foi diminuída (P<0,05) quando as tortas foram adicionadas. As tortas de nabo forrageiro e pinhão manso podem ser utilizadas em pequenas quantidades na ensilagem do capim-elefante por melhorarem as características químicas e fermentativas das silagens. Contudo, a torta de pinhão manso apresenta limitações para alimentação animal, pois apresenta compostos tóxicos, sendo necessários estudos para sua identificação e eliminação.
Composição química e características fermentativas de silagens de capim elefante contendo coprodutos da indústria do biodiesel
Keywords: ensilage; in vitro digestibility; Jatropha curcas; Pennisetum purpureum; Raphanus sativus